Subchondral involvement in osteonecrosis of the femoral head: insight on local composition, microstructure and vascularization. Issue 8 (August 2022) - Pascart, T.; Falgayrac, G.; Cortet, B.; Paccou, J.; Bleuse, M.; Coursier, R.; Putman, S.; Quinchon, J.-F.; Bertheaume, N.; Delattre, J.; Marchandise, P.; Cultot, A.; et al.
Summary: Objective: To determine changes of subchondral bone composition, micro-structure, bone marrow adiposity and micro-vascular perfusion in end-stage osteonecrosis of the femoral head (ONFH) compared to osteoarthritis (OA) using a combined in vivo and ex vivo approach. Design: Male patients up to 70 years old referred for total hip replacement surgery for end-stage ONFH were included ( n = 14). Fifteen patients with OA were controls. Pre-operative MRI was used to assess bone perfusion (dynamic contrast-enhanced (DCE) sequences) and marrow fat content (chemical shift imaging). Three distinct zones of femoral head subchondral bone – necrotic, sclerotic, distant – were compared between groups. After surgery, plugs were sampled in these zones and Raman spectroscopy was applied to characterize bone mineral and organic components (old and newly-formed), and contrast-enhanced micro-computed tomography (CE-μCT) to determine bone micro-structural parameters and volume of bone marrow adipocytes, using conventional 2D histology as a reference. Results: In the necrotic zone of ONFH patients compared to OA patients: 1) the subchondral plate did not exhibit significant changes in composition nor structure; 2) the volume fraction of subchondral trabecular bone was significantly lower; 3) type-B carbonate substitution was less pronounced, 4) collagen maturity was more pronounced; and 5 ) bone marrow adipocytes were significantly depleted. The sclerotic zone from the ONFH group showed greater trabecular thickness, and higher DCE-MRI AUC and Ktrans . Volume fraction of subchondral bone, trabecular number, and Kep were significantly lower in the distant zone of the ONFH group. Conclusions: This study demonstrated alterations of subchondral bone microstructure, composition, perfusion and/or adipose content in all zones of the femoral head.